2012
DOI: 10.1590/s0101-31222012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Viability of barley seeds by the tetrazolium test

Abstract: -The tetrazolium test is used to control seed quality of various plant species since it allows a rapid evaluation of viability. Freshly harvested barley seeds show dormancy that can make the germination test ineffective for an immediate evaluation. Therefore, the development of more efficient methods, such as the tetrazolium test, is necessary. The objective of this research work was to study various procedures for performing the tetrazolium test on barley seeds. Five lots of cv. BRS 195 barley seeds were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 8 publications
(1 reference statement)
2
17
0
9
Order By: Relevance
“…Estos resultados permitieron inferir que, cualquiera de estos tratamientos fue eficiente y confiable para determinar la viabilidad de las semillas de C. pyriformis, lo que es concordante con lo reportado por Grzybowski et al (2012) en Hordeum vulgare; por lo tanto, utilizar la solución de tetrazolio a concentraciones de 0,5% por dos horas, es más económico y permite una tinción adecuada de los tejidos de las semillas, sin perjudicar la visualización de la viabilidad. Resultados semejantes han sido sugeridos en las especies Acca sellowiana O. Berg Burret (Sarmento et al, 2013), Ceiba speciosa (Lazarotto et al, 2011), Copaifera langsdorffii, Schizolobium PG= porcentaje de germinación en cámara germinativa; C.V. = coeficiente de variación / ; PG = germination percentage found in germinative chamber; C.V. = coefficient of variation.…”
Section: Evaluación De Diferentes Concentraciones De Tetrazolio Y Tieunclassified
“…Estos resultados permitieron inferir que, cualquiera de estos tratamientos fue eficiente y confiable para determinar la viabilidad de las semillas de C. pyriformis, lo que es concordante con lo reportado por Grzybowski et al (2012) en Hordeum vulgare; por lo tanto, utilizar la solución de tetrazolio a concentraciones de 0,5% por dos horas, es más económico y permite una tinción adecuada de los tejidos de las semillas, sin perjudicar la visualización de la viabilidad. Resultados semejantes han sido sugeridos en las especies Acca sellowiana O. Berg Burret (Sarmento et al, 2013), Ceiba speciosa (Lazarotto et al, 2011), Copaifera langsdorffii, Schizolobium PG= porcentaje de germinación en cámara germinativa; C.V. = coeficiente de variación / ; PG = germination percentage found in germinative chamber; C.V. = coefficient of variation.…”
Section: Evaluación De Diferentes Concentraciones De Tetrazolio Y Tieunclassified
“…The same could be observed for seeds of peanut (Arachis hypogaea L.) ; black oat (Avena strigosa Sckreb.) and white oat (Avena sativa L.) (Souza et al, 2009(Souza et al, , 2010 and barley (Hordeum vulgare L.) (Grzybowski et al, 2012). However, the concentration is also related to the time of seed exposure to the solution and they usually exhibit an inversely proportional relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors also identified the possibility of reduction in the concentration of tetrazolium solution for other species such as the crambe (Rezende et al, 2015), forage turnip , Araucaria angustifolia (Oliveira et al, 2014), sunflower (Silva et al, 2013), barley (Grzybowski et al, 2012), triticale (Souza et al, 2010), black oats ) and castor beans (GasparOliveira et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have approached the appropriateness of the tetrazolium test methodology for seeds of different species such as Barbados nut (Pinto et al, 2009), castor beans (Gaspar-Oliveira et al, 2009), triticale (Souza et al, 2010, barley (Grzybowski et al, 2012), wheat (Carvalho et al, 2013), sunflower (Silva et al, 2013), sorghum , crambe (Rezende et al, 2015) and forage turnip .…”
Section: Introductionmentioning
confidence: 99%